PEMBELAJARAN MASA PANDEMI COVID–19: PERENCANAAN, PELAKSANAAN DAN EVALUASI - Kurniawan, Diki; Karim, Abdul; Komari, Komari (Program Studi Manajemen Pendidikan FKIP Universitas Cenderawasih, 2021)
The COVID-19 pandemic led to a policy of changing the learning system from offline to online. This policy has an impact on schools in Jayapura City, Papua. The purpose of this study was to analyze the implementation of learning in schools during the pandemic. Data retrieval using the triangulation method with research subjects came from representatives of kindergarten, elementary, and junior high school educators as well as representatives of the al-barakah foundation. The results of this study indicate that the principal in planning learning begins by holding In House Training which discusses the mechanism of implementing learning for one semester. In addition, making standard operating procedures for various activities. The implementation of learning experienced a reduction in teaching time and a reduction in extracurricular activities and other student self-development activities. Furthermore, the evaluation of learning carried out is based on information technology that utilizes the internet network. However, there is a school decision regarding the learning material taught to students in the form of essential material so that some material is not conveyed. This will result in a decrease in the quality of the material conveyed to students and the loss of one of the materials in certain subjects.Keywords: Planning; implementation; evaluation; covid-19 pandemic